Seeking the significance of music education essays and reflections - Reimer, Bennett (Rowman & Littlefield Education, 2009)
"Noted music educator Bennett Reimer has selected 24 of his previously published articles from a variety of professional journals spanning the past 50 years. During that time, he's tackled generating core values for the field of music education; the core in larger societal and educational contexts; what to teach and how to teach it effectively; how we need to educate our teachers; the role of research in our profession; and how to improve our future status."--Provided by publisher.